Eigenspaces of Hamming graphs and unitary Cayley graphs - Sander, Torsten (Ars mathematica contemporanea, 2010)
In this work, the eigenspaces of unitary Cayley graphs and certain Hamming graphs are considered. It is shown that these graph classes are closely related and admit particularly simple eigenspace bases for all eigenvalues, namely bases containing vectors only with entries from the set ?$\{0,1,-1\}$? A direct consequence is that the considered graph classes are integral.
Keywords: matematika; teorija grafov